2010
DOI: 10.1007/s00419-010-0479-7
|View full text |Cite
|
Sign up to set email alerts
|

Interface conditions simulating influence of a thin elastic wedge with smooth contacts

Abstract: The paper presents a method for deriving interface conditions simulating the influence of a thin wedge in a multi-wedge system with smooth contacts. It consists in successive (i) employing the Mellin's transform, (ii) separation of the symmetric and anti-symmetric parts of a solution, (iii) distinguishing terms tending to infinity, when the wedge angle tends to zero, (iv) appropriate re-arrangement of the terms to avoid degeneration, (v) using truncated power series in equations for the thin wedge and (vi) ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Often these additional identifications are for more complex local configurations than those in the references in the cited reviews: sometimes they simply fill in a gap in the literature. For classical elasticity with local configurations comprised of isotropic and piecewise homogeneous, linear elastic materials, all the stress singularities asymptotically identified that have been found to date since 2004 are discussed in the studies . Examples of stress singularities identified since 2004 for anisotropic elastic materials are given in the previous studies ; for functionally graded elastic materials; for finite strain in elastic materials; and for varying size scales …”
Section: Stress Singularity Identification: Asymptotic Analysismentioning
confidence: 94%
“…Often these additional identifications are for more complex local configurations than those in the references in the cited reviews: sometimes they simply fill in a gap in the literature. For classical elasticity with local configurations comprised of isotropic and piecewise homogeneous, linear elastic materials, all the stress singularities asymptotically identified that have been found to date since 2004 are discussed in the studies . Examples of stress singularities identified since 2004 for anisotropic elastic materials are given in the previous studies ; for functionally graded elastic materials; for finite strain in elastic materials; and for varying size scales …”
Section: Stress Singularity Identification: Asymptotic Analysismentioning
confidence: 94%
“…The authors reported that in this case (i) there was no complex roots of the characteristic determinant, and (ii) the singularity was not stronger than the inverse root of the distance d to the wedge apex. No complex roots were reported later for the Coulomb law of dry friction by Gdoutos and Theocaris (1975), Comninou (1976) and Churchman et al (2004), and for an arbitrary system with frictionless contacts by Linkov and Rybarska-Rusinek (2010). Meanwhile, the extended studying has shown that in some cases the power of the singularity may be stronger than Oð1= ffiffiffi d p Þ both for dry friction (Churchman et al, 2004) and for smooth contacts (Linkov and Rybarska-Rusinek, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…No complex roots were reported later for the Coulomb law of dry friction by Gdoutos and Theocaris (1975), Comninou (1976) and Churchman et al (2004), and for an arbitrary system with frictionless contacts by Linkov and Rybarska-Rusinek (2010). Meanwhile, the extended studying has shown that in some cases the power of the singularity may be stronger than Oð1= ffiffiffi d p Þ both for dry friction (Churchman et al, 2004) and for smooth contacts (Linkov and Rybarska-Rusinek, 2010). For the Coulomb friction law, it depends on the slip direction what is of importance for fretting problems (Churchman et al, 2004;Mugadu et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations